Optimization of the extraction of phenolic compounds from chestnut tree flowers - Caleja, Cristina (2018)
The chestnut tree fruits represent one of the most economically important agro-food material in the northeaster region of Portugal. Tones of bio-residues are generated annually (branches, leaves, flowers, etc) and used, in the better cases, as natural fertilizers or, in a less environmental friendly cases, burned. Otherwise, scientific reports have been relating the consumption of some synthetic compounds present in foods with undesirable effects on the human health. Such results are pushing the food-industry to look for alternatives that meet consumer needs towards a more natural market. Therefore, the aim of this work was to valorise chestnut flowers’ (CF) bio-residues and to develop a profitable natural antioxidant. Although less exploited for economical purposes, CF have been used since ancient times in the preparation of infusions due to the high concentration of active phenolic compounds (PC) beneficial to the human health. Recent research has shown that CF possesses high abundance of PC that can be used in the preservation of foods due to their capacity to inhibit lipid peroxidation and microbial proliferation. However, to compete with the price-value of synthetic antioxidants typically applied, the PC extracted from CF need to be maximized. Therefore, the conditions of time (t), temperature (T) and solvent (S) that favours the extraction by maceration of PC were optimized by response surface methodology using a 5-level experimental design. The responses used as criteria were the quantification of the fourteen individual PC by HPLC-DAD and the extraction yield of the obtained extract (E). The models developed were successfully fitted to the data and used to determine optimal extraction conditions (t= 120.0±12.4 min, T= 85.0±6.7 ºC and S= 44.5 % of ethanol) producing 55.37±2.20 mg PC/g E. The results highlight the potential of valorising CF bio-residues as a productive source of PC for the development of a natural preservative that may be able to compete with synthetic compounds typically applied in the food-industry.